2019
DOI: 10.18517/ijaseit.9.3.7612
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Pectin Extracted from Selected Local Fruits By-Product

Abstract: Pectin was extracted from selected local fruits by-product, which was a banana, mango, and papaya peel by using the citric acid solution as a solvent. The primary objectives of this study were to extract pectin from selected local fruits by-product as well as, to determine and compare the physicochemical properties of extracted pectin to that of commercial pectin. Pectin extracted from mango peel gave the highest yield significantly (15.4%) as compared to banana peel pectin (14.47%) and papaya peel pectin (12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
0
0
Order By: Relevance
“…These data confirmed that there was a reduction in the solubility of the pectins extracted from dragon fruit peels as compared with the commercial one. This outcome was also aligned with previous work applied on mango, papaya or banana peels (Fmna & Zailan, 2019).…”
Section: Resultssupporting
confidence: 88%
“…These data confirmed that there was a reduction in the solubility of the pectins extracted from dragon fruit peels as compared with the commercial one. This outcome was also aligned with previous work applied on mango, papaya or banana peels (Fmna & Zailan, 2019).…”
Section: Resultssupporting
confidence: 88%
“…Study by Sangheetha et al (2018) on pectin extraction from mango peel collected from mango processing industry reported pectin yield ranging from 6.12 to 16.3 per cent with different combinations of pH (1.3, 2.5 and 3.7), temperature (60, 75 and 90C) and time (45, 90 and 135 minutes).The findings of the present study commemorate with that reported by Aida and Zailan (2019), who reported pectin yield of 15.4 per cent from mango peel powder extracted by using 0.1 N HCL at 70C for 75 minutes and precipitated by 95 per cent ethanol. Similarly, Ismail et al (2012) reported pectin yield of 14.96 per cent from dragon fruit peel extracted with different pH, acid and temperature levels.…”
Section: Pectin Extraction Yieldsupporting
confidence: 87%
“…Solubility of mango peel pectin ranged from 80 to 98.3 per cent in a study reported by Aida and Zailan (2019).…”
Section: Solubilitymentioning
confidence: 91%